Multicriteria decision making in organic-metal frameworks for fuel storage - Balo, Figen; Sua, Lutfu S. (Elsevier, 2022)
Due to the simple and fast division of electrons and ions via the pores, the porous materials are commonly used in different fields. Porous materials include porous ceramics, porous glass, polymer foams, activated carbon, zeolites, and porous metals; recent attention has been drawn to metal-organic frames among these materials. Organic-metal frameworks are a porous, inorganic-organic hybrid combination in which an organic ligand and a metal ion are joined together to form a 3D structure through coordination. Acetylene and methane show more environmental fuels, which are regarded as perfect options to fossil fuels. Owing to volumetrically low power density at atmospheric circumstances, it is greatly satisfactory to improve porous materials like organic-metal frameworks that indicate high adsorption features on this basis them. In this study, the improvement history on the synthesis and design of porous organic-metal frameworks for methane and acetylene storage is investigated. The methane adsorption features of those favorable organic-metal frameworks are reviewed in conjunction with the pore textural features over the last decade. The aim of this paper is to initiate a quantitative model approach for the determination of relevant factors for the creation of a comparison basis for the methane adsorption features in organic-metal frameworks for fuel storage. For the purpose of this analysis, the relative priorities of the chosen variables will be calculated on the basis of expert opinions. The number of variables can be raised in a following research and their relative goals can be adjusted based on novel perspectives. Furthermore, this study supplies a comprehensive conspectus on the efficiency of the methane adsorption features for fuel storage utilizing metal-organic framework materials. © 2022 Elsevier Inc. All rights reserved.
Keywords: Data analysis; Fuel storage; Metal-organic frameworks; Methane